1996
DOI: 10.1007/bf00015307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizae on heavy metal (Zn and Pb) uptake and growth of Lygeum spartum and Anthyllis cytisoides

Abstract: The influence of arbuscular mycorrhizae (AM) on plant growth and Zn and Pb uptake by Lygeum spartum and Anthyllis cytisoides was studied in soils with different levels of these heavy metals. A. cytisoides is highly dependent on AM for optimal growth, while L. spartum is a facultative mycotroph.Mycorrhizal and nonmycorrhizal plants were grown in soil supplemented with 0, 10, 100 and 1000 mg of Zn kg -l soil or 0, 100 and 1000 mg of Pb kg -1 soil. Two different mycorrhizal fungi were separately studied: Glomus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 33 publications
9
66
0
12
Order By: Relevance
“…In line with our results, other researchers also reported that inoculation of plants with AMF increased uptake of N, P, K, Zn, Fe, Cu, Mg and Ca (Tinker and Gildon 1983;Díaz et al 1996). The results are also supported by the results reported by Aziz and Khan (2001), which showed that coinoculation of alfalfa with Glomus mosseae and Sinorhizobium meliloti increased N and P contents in the plant tissues.…”
Section: Discussion Nutrientssupporting
confidence: 92%
“…In line with our results, other researchers also reported that inoculation of plants with AMF increased uptake of N, P, K, Zn, Fe, Cu, Mg and Ca (Tinker and Gildon 1983;Díaz et al 1996). The results are also supported by the results reported by Aziz and Khan (2001), which showed that coinoculation of alfalfa with Glomus mosseae and Sinorhizobium meliloti increased N and P contents in the plant tissues.…”
Section: Discussion Nutrientssupporting
confidence: 92%
“…High levels of colonization by AM fungi were observed both in mine spoils heavily polluted with metals by Diaz et al (1996) and in agricultural soils contaminated with metals of different origins by Weissenhorn et al (1995a,b). This leads to the conclusion that metal tolerance has developed naturally in the soil microorganisms.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of mycorrhizae also seems to be related to the formation of thiol like glutathione (Schutzendubel & Andrea, 2002), a phenolic defense system. It is hypothesized that the production of thiols by P. vittata, induced by the increased arsenic concentration, alleviates the toxicity of arsenic and the plant can readily retain arsenic with the aid of mycorrhizas (Diaz et al, 1996). Therefore, it is possible that P. vittata may derive some benefit from the symbiosis by forming low molecular weight thiols.…”
Section: Arsenic Species In Ferns -mentioning
confidence: 99%